Design guidelines for an electron diffractometer for structural chemistry and structural biology. Issue 5 (7th May 2019) - Heidler, Jonas; Pantelic, Radosav; Wennmacher, Julian T. C.; Zaubitzer, Christian; Fecteau-Lefebvre, Ariane; Goldie, Kenneth N.; Müller, Elisabeth; Holstein, Julian J.; van Genderen, Eric; De Carlo, Sacha; Gruene, Tim
Abstract : Installation of the EIGER X 1M detector onto an electron microscope and system calibration for data collection turns a transmission electron microscope into an electron diffraction instrument. Data can be collected and processed with a throughput that meets the requirements of a modern X‐ray facility. The setup described here offers access to single‐crystal structure determination from microcrystalline powder when large single crystals cannot be produced. Abstract : 3D electron diffraction has reached a stage where the structures of chemical compounds can be solved productively. Instrumentation is lagging behind this development, and to date dedicated electron diffractometers for data collection based on the rotation method do not exist. Current studies use transmission electron microscopes as a workaround. These are optimized for imaging, which is not optimal for diffraction studies. The beam intensity is very high, it is difficult to create parallel beam illumination and the detectors used for imaging are of only limited use for diffraction studies. In this work, the combination of an EIGER hybrid pixel detector with a transmission electron microscope to construct a productive electron diffractometer is described. The construction not only refers to the combination of hardware but also to the calibration of the system, so that it provides rapid access to the experimental parameters that are necessary for processing diffraction data. Until fully integrated electron diffractometers become available, this describes a setup for productive and efficient operation in chemical crystallography.